Iodine status and characteristics of Korean adolescents and their parents based on urinary iodine concentration: a nationwide cross-sectional study - Yun Chang Choi; Ji In Cheong; Hee Won Chueh; Jae-Ho Yoo (Korean Society of Pediatric Endocrinology, 2019)
Purpose Iodine is a major component of thyroid hormones. Both deficiency and excess of iodine are major risk factors for thyroid disease, making it important to accurately assess iodine level in the human body. Urinary iodine concentration (UIC) is a commonly used measure of iodine status. However, there is little research on iodine status and related characteristics in Korean adolescents. Methods Using data from the sixth Korea National Health and Nutrition Examination Survey (KNHANES VI) for the years 2013-2015, we analyzed UIC and thyroid function test results in adolescents aged 10-18 years and their parents. We also investigated the influence of socioeconomic factors and family history of thyroid disease on iodine status. Results Mean UIC in Korean adolescents was 963.5±55.7 μg/L. Among evaluated subjects, 6.6%±1.0%, 29.8%±1.7%, and 63.9%±1.9% had low (UIC<100 μg/L), adequate (UIC: 100-299.9 μg/L), and excess (UIC≥300 μg/L) iodine concentrations, respectively. Based on regional trends, the incidence of iodine deficiency exceeded 10% in several regions, even though there was a dominance of regions with excess iodine. Parental UIC, female sex, average monthly income, and expenditure were all found to affect the iodine status of Korean adolescents. Conclusions Although regional differences exist, the iodine status in Korean adolescents is mainly affected by the eating habits of their families and socioeconomic factors. Therefore, monitoring of iodine status is necessary in this population.